From Ancient Wisdom to Modern Health: ’Let Food Be Thy Medicine’ – Examining the Cardiovascular Impact of Ghee and Seed Oils" - Anamika, FNU; Mahajan, Sidharth; Munjal, Parth; Aggarwal, Kanishk; Jain, Rohit (Eastern Journal of Medical Sciences, 2025)
Diet and eating habits are closely linked to overall health, particularly cardiovascular well-being. In recent years, there has been a growing trend in the consumption of ghee (clarified butter) and seed oils (vegetable oils derived from plant seeds such as corn, soybeans, sunflower, and peanuts). While concerns have been raised due to their high-fat content, both ghee and seed oils contain bioactive compounds with potential health benefits. Ghee is a rich source of fat-soluble vitamins—A, D, E, and K—and also contains short-chain and medium-chain fatty acids that may have anti-inflammatory and lipid-modulating effects. Some studies suggest that moderate ghee consumption may improve HDL levels and reduce LDL oxidation, potentially lowering the risk of atherosclerosis. Conversely, seed oils are high in Omega-6 and Omega-3 polyunsaturated fatty acids (PUFAs), which are known to support endothelial function and reduce systemic inflammation when consumed in appropriate ratios. This narrative review aims to assess and compare the effects of ghee and seed oil intake on cardiovascular disease risk, drawing on current scientific literature to clarify their respective roles in cardiovascular health and disease prevention.